Revitalisasi Dalam Fluktuasi Kesenian Reog Ponorogo Menuju Icon Kabupaten Daerah Tingkat II Ponorogo - Luh Putu Kerti Pujani (Institut Seni Indonesia Denpasar, 2009)
The art performance know as Reog Ponorogo is based on folklore which is certainty believed by Ponorogo Community. Reog Ponorogo consists of historical/ancestral values which are represented through specific symbols in that art performance. In it’s development Reog Ponorogo has diachronic side, fluctuated between growth and fall, well described as alienated and marginalized. Those situations were caused by domination of colonial government and political movement. The turning point was made by ingenuity of traditional Muslim student that performed “gajah-gajahan” art performance which similar to act of Reog in the period of the second fall phase caused by domination of colonial regime. Nowadays, the intensity of revitalization, contruction, reproduction is conducated by preserving the dance on village community level and also revotalization action formally by The Ponorogo regency. Thus, Reog is reproduced to achieve a distinctive existence and becomes an icon of Ponorogo area.